Effect of a Park-Based After-School Program on Participant Obesity-Related Health Outcomes. Issue 4 (March 2015) - Messiah, Sarah E.; Diego, Allison; Kardys, Jack; Kirwin, Kevin; Hanson, Eric; Nottage, Renae; Ramirez, Shawn; Arheart, Kristopher L.
Purpose: The objective of this study was to examine the effect of a structured after-school program housed in a large county parks system on participant health and wellness outcomes. Design: Longitudinal cohort study over one school year (fall 2011-spring 2012). Setting: A total of 23 county parks in Florida. Subjects: Children ages 5 to 16 (N= 349, 55% non-Hispanic black, 40% Hispanic, mean age 8.9 years). Intervention: An after-school program called Fit-2-Play that integrates daily standardized physical activity and health and wellness education components. Measures: Preintervention (August/September 2011) and postintervention (May/June 2012) anthropometric, systolic/diastolic blood pressure, fitness, and health and wellness knowledge measurements were collected. Analysis: Comparison of pre-post outcome measure means were assessed via general linear mixed models for normal-weight (body mass index [BMI] < 85th percentile for age and sex) and overweight/obese (BMI ≥85th percentile for age and sex) participants. Results: The overweight/obese group significantly decreased their mean (1) BMI z score (2.0 to 1.8, p < .01) and (2) subscapular skinfold measurements (19.4 to 17.5 mm, p < .01) and increased (1) mean laps on the Progressive Aerobic Cardiovascular Endurance Run test (10.8 to 12.5, p = .04) and (2) percentage with normal systolic blood pressure (58.1% to 71.0%, p = .03) from pretest to posttest. On average, participants significantly improved their health and wellness knowledge over the school year (p < .01). Normal-weight participants maintained healthy BMI ranges and significantly increased fitness levels. Conclusion: Findings suggest that the Fit-2-Play after-school programs can be a significant resource for combating childhood obesity and instilling positive physical health in children, particularly among ethnic and socioeconomically diverse communities.